2015
DOI: 10.1179/1743294414y.0000000413
|View full text |Cite
|
Sign up to set email alerts
|

Study on fabrication of ceramic coatings on Ti–6Al–4V alloy by combined ultrasonic impact treatment and electrospark

Abstract: A method combining ultrasonic impact treatment with electrospark was developed to fabricate ceramic coatings on Ti-6Al-4V alloy. In this paper, the mechanism of the combined process is described in detail. The microstructure, chemical states, phase composition and surface residual stress of the ceramic coated titanium alloy were presented. The coatings mainly consist of carbides of titanium. The hardness of the coating increased significantly owing to the existence of the ceramic phase. Further, the impact pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The UIT induced hardening of 2024 alloy was explained by the formation of fine grains [16]. In our case, the deformation induced mechano-chemical reactions [15,16] and the formation of the oxide/intermetallic layer [16,20,21] significantly increase the hardness of the surface after the air-UIT process. The XRD analysis confirmed that simultaneous mass-transfer of oxygen and iron in the surface layer facilitates the formation of the complex iron aluminium oxides like spinels FeAl 2 O 4 , AlFeO 3 (Figure 3).…”
Section: Resultsmentioning
confidence: 87%
“…The UIT induced hardening of 2024 alloy was explained by the formation of fine grains [16]. In our case, the deformation induced mechano-chemical reactions [15,16] and the formation of the oxide/intermetallic layer [16,20,21] significantly increase the hardness of the surface after the air-UIT process. The XRD analysis confirmed that simultaneous mass-transfer of oxygen and iron in the surface layer facilitates the formation of the complex iron aluminium oxides like spinels FeAl 2 O 4 , AlFeO 3 (Figure 3).…”
Section: Resultsmentioning
confidence: 87%
“…One of the promising techniques for improving wear resistance of the Ti-6Al-4V alloy is a method based on a combination of ultrasonic impact treatment with electrospark alloying [18][19][20][21]. As a result of ultrasonic impact electrospark treatment (UIET), continuous hard coatings are formed on the Ti-6Al-4V alloy surface, uniform in thickness and consisting of small drops of the striker (anode) material.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted by Liu et al [9][10][11] combined the advantage of UIT and ESD, a new method named ultrasonic impact electro-spark treatment (UIET) was proposed, and its feasibility for the preparation of coatings on Ti-6Al-4V (TC4) was investigated. In the UIET, the target and shock ball are connected to the cathode and anode, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The surface roughness and wear properties of specimens under untreated, UIT and UIEMT conditions were investigated in the following. The previous approach [10,11] is referred as ultrasonic impact electro-spark deposition treatment (UIEDT) in order to avoid any confusion.…”
Section: Introductionmentioning
confidence: 99%